SmartElectra: Sistem Cerdas Pengendali Aliran Listrik Berbasis Android untuk Otomasi Rumah Modern - Ida Ernawati; Trisno Sanyoto; Setyo Hartono; Lawrence Adi Supriyono (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
In the digital transformation era, the demand for automation in household electrical systems continues to grow to improve energy efficiency and user convenience. Traditional manual control of electrical devices is considered inefficient and lacks integration with current smart technologies. This research addresses the problem by designing a smart electrical control system, SmartElectra, which allows users to remotely monitor and control the flow of electricity using an Android-based application. The system integrates the ESP32 microcontroller, a relay module, and a Wi-Fi network to receive and execute commands from the mobile application. The Android interface was developed using MIT App Inventor, enabling seamless wireless communication with the hardware. Testing was conducted to evaluate the system’s responsiveness, control accuracy, and communication range in a typical residential setting. Results show that SmartElectra effectively controls electrical loads with an average response time of 1.2 seconds and reliable operation within a 20-meter range. With its dual-core processing power and built-in wireless capabilities, the ESP32 provides a robust and scalable foundation for smart home applications. This system presents a cost-effective, user-friendly solution that enhances energy management and remote control in modern households.